2000
DOI: 10.1002/(sici)1097-4652(200004)183:1<83::aid-jcp10>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine kinase inhibitors increase cytosolic calcium and inhibit actin organization as resorbing activity in rat osteoclasts

Abstract: Although there is evidence that protein tyrosine kinase inhibitors (PTKIs) suppress bone resorption activity, the mechanism of action of these compounds on osteoclastic bone resorption remains obscure. In the present study, we investigated the effect of PTKIs on cytosolic Ca(2+) concentration ([Ca(2+)](i)) and on the cytoskeleton in rat osteoclasts. The PTKIs, genistein and herbimycin A, reversibly elevated [Ca(2+)](i) measured by fura-2 microfluorimetry. The PTKI-induced increase was abolished by omission of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
4
30
1
Order By: Relevance
“…Similar considerations apply to the stimulators, e.g. PTH, where our experimental data show a rise, fall or no effect on the osteoclast cytosolic Ca 2+ , the variety of responses produced being determined by the extent and kinetics of stimulation of efflux and influx by the particular agent (Zaidi et al 1990, MacIntyre et al 1991, Bizzari et al 1994, Rathod et al 1994, Parkinson et al 1998, Kajiya et al 2000, Berger et al 2001. The above arguments are valid and applicable both for bulk transcytosis as well as to selective uptake involving specialised Ca 2+ channels.…”
Section: Anomaly Of Cytosolic Ca 2+ Transientssupporting
confidence: 71%
See 2 more Smart Citations
“…Similar considerations apply to the stimulators, e.g. PTH, where our experimental data show a rise, fall or no effect on the osteoclast cytosolic Ca 2+ , the variety of responses produced being determined by the extent and kinetics of stimulation of efflux and influx by the particular agent (Zaidi et al 1990, MacIntyre et al 1991, Bizzari et al 1994, Rathod et al 1994, Parkinson et al 1998, Kajiya et al 2000, Berger et al 2001. The above arguments are valid and applicable both for bulk transcytosis as well as to selective uptake involving specialised Ca 2+ channels.…”
Section: Anomaly Of Cytosolic Ca 2+ Transientssupporting
confidence: 71%
“…A number of diverse agents, such as calcitonin (CT), interleukin-4 (IL-4), protein tyrosine kinase inhibitors and elevated extracellular [Ca 2+ ], which acutely increase [Ca 2+ ] i , inhibit the osteoclast (Bizzari et al 1994, Rathod et al 1995, Kajiya et al 2000, Berger et al 2001. Indeed, an increase in [Ca 2+ ] i has been generally accepted as a potential mechanism by which various agents inhibit osteoclastic activity.…”
Section: Anomaly Of Cytosolic Ca 2+ Transientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that soy isoflavones can increase bone mineral content and bone density in humans [15,17]. Genistein has been shown to increase proliferation and differentiation of osteoblast-like cells and collagen synthesis [9] and decrease intracellular Ca concentrations in osteoclasts in animals [16,23]. Yamaguchi and Gao [39] reported that genistein has an anabolic effect on bone mineralization in the tissue culture system.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major soy isoflavones, genistein has been shown to increase osteoblast proliferation/ differentiation, alkaline phosphatase (ALP) activity and collagen synthesis, but inhibits the recruitment and function of osteoclasts [15]. Genistein also causes elevation in intracellular calcium concentrations and decreases phosphorylation in osteoclasts [16,23].…”
Section: Introductionmentioning
confidence: 99%